Retrorectal tumors: report of two cases - Kafle, P; Praveen, CR; Kumar, S; Patowary, BN; Maharjan, N; Shah, S; Agrawal, S (Journal of College of Medical Sciences-Nepal, 2013)
Retrorectal tumor is uncommon identity presenting with nonspecific sign and symptoms making difficulty in diagnosis. Benign tumors are more common than malignant. The lesion may be malignant or progress to malignancy from benign state. Retrorectal masses in young women may continue to grow and result in dystocia. Cystic lesions are also at risk of becoming infected, which renders subsequent excision more difficult and increase the risk of recurrence. Cross-sectional imaging is required to determine the extent of resection and the appropriate surgical approach. Surgical removal leads to favorable outcomes for patients with benign purely cystic retrorectal tumors. We report two such benign rectal lesions. ] Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 46-50 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8701